Investigations of the mode of action of a new antidysrhythmic drug, Kö 1173 - Singh, B. N. (1972)
1. Kö 1173, 1-(2',6'-dimethyl-phenoxy)-2-amino-propane, was equal to lignocaine in potency as a local anaesthetic on stripped frog sciatic nerve at pH 7·5. 2. In anaesthetized guinea-pigs in which ventricular fibrillation had been produced by an intravenous infusion of ouabain, intravenous administration of Kö 1173 caused reversion to sinus rhythm in ten out of ten animals. The mean dose of Kö 1173 required was 3·3 mg (15·3 μmol)/kg. When the ouabain infusion was continued, ventricular fibrillation did not recur, and the lethal dose of ouabain was greater than in controls. 3. Pretreatment with Kö 1173, however, did not influence the toxicity of ouabain infusion, implying great brevity of action. 4. Kö 1173 given intravenously caused a bradycardia which was maximal in 2-3 min, and which did not last more than 5 minutes. 5. Kö 1173 reduced the maximum driven frequency of isolated rabbit atria, raised electrical threshold, slowed conduction velocity and depressed contractions. 6. Kö 1173 reduced the maximum rate of depolarization of intracellularly recorded rabbit atrial and ventricular potentials, but did not affect the resting potential or the duration of the action potential.